Thromboprophylaxis in medical patients: the role of low-molecular-weight heparin - Alexander, Turpie G. G.; Norris, Timothy M. (Thrombosis and Haemostasis, 2004)
Many hospitalised medical patients are at increased risk of venous thromboembolism (VTE). Consensus statements recommend that such patients be assessed for risk of VTE on admission to hospital and receive thromboprophylaxis where appropriate. However, VTE prophylaxis is not widely used in medical patients. One explanation is that assessing medical patients’ risk of VTE is complicated. The risk depends not only on the current illness but also on multiple intrinsic factors, and a variety of strategies for identifying patients who should receive thromboprophylaxis have been suggested. Thromboprophylaxis with unfractionated heparin (UFH) has proved to be effective in reducing the incidence of deep-vein thrombosis and overall mortality in medical patients. Clinical trial evidence, including a meta-analysis, suggests that thromboprophylaxis with low-molecular-weight heparin (LMWH) is at least as effective as with UFH, and also has the advantage of fewer bleeding complications. In particular, two large, randomised clinical trials – Prophylaxis in Medical Patients with Enoxaparin (MEDENOX) and Prospective Evaluation of Dalteparin Efficacy for Prevention of VTE in Immobilized Patients Trial (PREVENT) – showed that thromboprophylaxis with the LMWHs enoxaparin (40 mg s.c. once daily) or dalteparin (5,000 IU once daily) is more effective than placebo and well tolerated in medical patients. In addition, the Thromboembolism-Prevention in Cardiopulmonary Diseases with Enoxaparin (THE-PRINCE) trial showed that enoxaparin treatment was as effective as UFH. These studies provide solid evidence for the widespread use of thromboprophylaxis in medical patients.
Keywords: Venous thromboembolism; deep-vein thrombosis; pulmonary embolism; thromboprophylaxis; low-molecular-weight heparin; medical patients